Social Media: It’s Effect on Student Engagement - Hulwana, Halad; Roza, Veni (BiCED Proceeding, 2023)
Student engagement is the frequency of their participation in a learning program. This study aims to find out how social media affects student engagement. The student participants responded well to the flipped model of instruction and showed an increase in engagement and communication when compared to the traditional classroom setting, according to both quantitative and qualitative findings. (Clark, n.d.). The researcher chose whatsApp and Youtube in blended flipped classroom model since these media are so familiar with the students. This study used an experimental quantitative research design with thirty-two junior high school students as its population. Based on (Wang et al., 2014) utilizing the Classroom Participation Inventory to assess the students’ participation. Students respond on a Likert-style scale from 1 to 4, in which 1 indicates severe disagreement until 4 to state the strongly agreement. The results of this study indicate that learning with blended flipped classroom model through social media has an influence on student engagement.